Two new species of cheyletid mites (Acari: Prostigmata) from Thailand - Fuangarworn, Marut; Lekprayoon, Chariya (Zootaxa, 2010)
Two new species of predatory mites in the family Cheyletidae (Acari: Prostigmata), Mexecheles thailandensis n. sp. collected from tree bark infested by scolytid beetles and Samsinakia charanasriae n. sp. from soil and leaf-litter, are described and illustrated from Thailand. Keys to species of Mexecheles and Samsinakia are also provided.